Citrus leaf blotch virus invades meristematic regions in Nicotiana benthamiana and citrus. - Agüero, Jesús; Vives, María C.; Velázquez, Karelia; Ruiz-Ruiz, Susana; Juárez, José; Navarro, Luis; Moreno, Pedro; Guerri, José (2017)
To invade systemically host plants, viruses need to replicate in the infected cells, spread to neighbouring cells through plasmodesmata and move to distal parts of the plant via sieve tubes to start new infection foci. To monitor the infection of Nicotiana benthamiana plants by Citrus leaf blotch virus (CLBV), leaves were agroinoculated with an infectious cDNA clone of the CLBV genomic RNA expressing green fluorescent protein (GFP) under the transcriptional control of a duplicate promoter of the coat protein subgenomic RNA. Fluorescent spots first appeared in agroinfiltrated leaves 11-12 days after infiltration, indicating CLBV replication. Then, after entering the phloem vascular system, CLBV was unloaded in the upper parts of the plant and invaded all tissues, including flower organs and meristems. GFP fluorescence was not visible in citrus plants infected with CLBV-GFP. Therefore, to detect CLBV in meristematic regions, Mexican lime (Citrus aurantifolia) plants were graft inoculated with CLBV, with Citrus tristeza virus (CTV), a virus readily eliminated by shoot-tip grafting invitro, or with both simultaneously. Although CLBV was detected by hybridization and real-time reverse transcription-polymerase chain reaction (RT-PCR) in 0.2-mm shoot tips in all CLBV-inoculated plants, CTV was not detected. These results explain the difficulty in eliminating CLBV by shoot-tip grafting invitro.